Exploring the Impact of Punctuation Usage on Students’ Writing Skills - Ning Setio Wati (Jurnal Pedagogy, 2021)
Punctuation usage has an important role in creating effective writing in paragraphs. This article explored on how the students’ activity in using punctuation as an aspect of writing skill correctly. Twenty secondary students participated in this study to investigate how to employ punctuation usage correctly in their English writing skills. This is descriptive qualitative research. In this case, the researcher used observation and interviews to get the data. This research was conducted for three weeks from the end of November until the second week in December 2020. The finding from the study demonstrated that the students learned to be more inventive and skillful in using punctuation usage in their writing skills. However, some punctuation usage errors were being to support students in their produce paragraph. The implication of the study is discussed to students’ writing comprehensibility of graphic principles relative to linguistic principles